Beyond cholesterol metabolism: The pleiotropic effects of proprotein convertase subtilisin/kexin type 9 (PCSK9). Genetics, mutations, expression, and perspective for long‐term inhibition. (30th January 2020) - Cesaro, Arturo; Bianconi, Vanessa; Gragnano, Felice; Moscarella, Elisabetta; Fimiani, Fabio; Monda, Emanuele; Scudiero, Olga; Limongelli, Giuseppe; Pirro, Matteo; Calabrò, Paolo
Abstract: Proprotein convertase subtilisin/kexin type 9 (PCSK9) has a crucial role in lipid metabolism, particularly due to its function in low‐density lipoprotein receptor degradation. Gain‐of‐function genetic mutations of PCSK9 result in autosomal dominant familial hypercholesterolemia, characterized by high levels of low‐density lipoprotein cholesterol (LDL‐C) and clinical signs of early atherosclerosis. In recent years, PCSK9 has become an important therapeutic target for cholesterol‐lowering therapy. Particularly, its inhibition with monoclonal antibodies has shown excellent efficacy in decreasing LDL‐C and reducing cardiovascular events. However, PCSK9, first identified in the brain, seems to be a ubiquitous protein with different tissue‐specific functions also independent of cholesterol metabolism. Accordingly, it appears to be involved in the immune response, haemostasis, glucose metabolism, neuronal survival, and several other biological functions. This review provides a comprehensive overview of the genetics, biochemical structure, expression, and function of PCSK9 and discusses the potential implications of its long‐term pharmacological inhibition.